Synthesis, characterization and cytotoxic effect of 2-((E)-((E)-2-(5-chloro-3,3-dimethylindolin-2-ylidene)-3-oxopropylidene) amino) benzoic acid on the MCF7 cancer cell line: Cytotoxic Effect of Novel Indoline Derivative - Ghaidan, Aseel (Iraqi Journal of Cancer and Medical Genetics, 2025)
Indole Schiff base derivatives have attracted considerable interest in the field of medicinal chemistry because of their broad range of biological activities. This study aimed to synthesize a new indole Schiff base derivative, and its cytotoxic activity was subsequently tested against the MCF7 breast cancer cell line and the REF normal cell line. The new compound 2-((E)-((E)-2-(5-chloro-3,3-dimethylindolin-2-ylidene)-3-oxopropylidene) amino) benzoic acid was synthesized via the condensation reaction of malonaldehyde with 2-aminobenzoic acid in methanol under acidic conditions, as shown in Figure (1). The chemical structure of the synthesized compound was characterized by TLC, FT-IR, 1H NMR and 13C NMR, and the absorption bands confirmed the chemical structure of this new compound. The cytotoxic activity of the new synthetic Schiff base compound was studied by using a breast cancer cell line (MCF7) and a normal cell line (REF). The results revealed a low inhibition rate at low concentration on normal cells with 11% and 12% for 48 hrs. and with (40, 60) µg/ml concentration showed 16% and 22% for the same time. The cytotoxic activity of this compound toward MCF7 showed a higher inhibition rate with 64% for the concentration (60 µg/ml), 63% for (40 µg/ml), 60% for (20 µg/ml), and 56% for (10 µg/ml) after 48 hrs. Therefore, this new compound has high potential to inhibit MCF7 breast cancer cell line.